E-Infrastructure and e-Services : 7th International Conference, AFRICOMM 2015, Cotonou, Benin, December 15-16, 2015, Revised selected papers /: 7th International Conference, AFRICOMM 2015, Cotonou, Benin, December 15-16, 2015, Revised selected papers. (2016) - Unknown
No abstract available